49 Shockwave intravascular lithotripsy (ivl) for calcified coronary lesions; a real world multicentre european study with long term follow up. (6th June 2022) - Raja, Waseem; Testa, Luca; Popolo Rubbio, Antonio; Cortese, Bernardo; Wassef, Nancy; Raju, Prashanth; Sharma, Vinoda; Choudhury, Anirban; Hailan, Ahmed; Lelasi, Alfonso; Mastrangelo, Angelo; Bartorelli, Antonio; et al.
Abstract : Introduction: The presence of calcium in atherosclerotic plaques is a challenge for successful angioplasty and is an independent risk factor for restenosis and stent thrombosis. Despite conventional tools (non-compliant, scoring and cutting balloons and rotational atherectomy), cracking calcium can still be challenging and incomplete. Intra-vascular lithotripsy (IVL) has shown promising results, although long-term data on safety and efficacy from real-world is lacking. In this study, we report long-term outcomes following use of IVL from a European multi-centre experience. Methods: This was a multicentre, retrospective observational study in which we enrolled all patients treated with shockwave lithotripsy from November 2018 to June 2021. Procedural success, complications and in hospital events were evaluated. The clinical outcomes during follow-up included cardiac death, target vessel myocardial infarction (TVMI), target lesion revascularisation (TLR), and major adverse cardiac event (MACE) (composite of cardiac death, TVMI, and TVR). Result: A total of 272 patients were treated with IVL, with a mean age of 72 ± 9.1 years and 78.5% (n=216) were male. Forty percent (n=110) were diabetic while 16% (n=45) had chronic kidney disease. Acute coronary syndrome was the presentation in 36%(n=99) while 51%(n=141) had stable angina. De novo lesions accounted for 78% (n=215) of the cases and the remainder were in-stent restenosis (21%; n=58). The LAD was the commonest artery treated 50% (n=139) followed by RCA 24%(n=68). Intracoronary imaging was performed in 33% of cases. Upfront IVL strategy was adopted in 37%(n=101) while 63% (n=171) were bail out procedures due to inadequate predilatation. Adjuvant rotational atherectomy was used on 31 (11.4%) cases. Procedural success was achieved in 96% (260) cases with coronary perforation in 8 cases (3-cases needed covered stents). There was no in-hospital mortality. Clinical outcomes over the median follow up of 641-days (1.7 years) are shown in the table. Conclusion: This is the largest multicentre registry with long term follow up. It has demonstrated that IVL appears to be safe with high success rates, low rates of complication and no in-hospital mortality. The long-term follow-up show promising results with low rates of hard-endpoints and revascularization rates. Conflict of Interest: None